PENGARUH BALANCE EXERCISES TERHADAP KEKUATAN OTOT PADA LANSIA OFA PADANG MAHONDANG KECAMATAN PULAU RAKYAT KABUPATENASAHAN TAHUN 2020 - Friska Br Sembiring (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2020)
Agingor getting old is a process where changes are natural and accompanied by a decrease in physical, psychological, and social conditions. Where a significant decrease in function in the elderly, this goal reveals that routine balance exercise can cause muscle loss in the elderly. The result shows that the frequency distribution of the effect of Balance Exercixe on Muscle Strength in Lansi where the muscle strength before doing Balance Exercises movement experiences good muscle strength (-%), while after doing Balance Exercixe there is a change to around (80%). Based on the results of Wilcoxon calculations signed rank test, the value obtained is -3448 with a P Value (Asymp. Sig 2 tailed) of 0.001 which is less than the critical research limit of 0.05 so that the hypothesis decision is to accept H1 or which means there is a significant difference between before and after making the balance .